Theoretical and Instrumental Principles of the Migration (Economics and region, 2020)
Main theoretical aspects of migration are considered. It is noted that if labour migration is effectively coordinated, properly managed and strongly regulated can be of a profound benefit for both host and home country by reducing the disparity between where there is a labour deficit and a labour surplus, it can also lead to domestic business development through both foreign direct investment of financial resources as well as human resources. Since the last century migration topic has been a hot topic because over the last few decades we have seen countless number of people migrating from the third world countries to the first world countries in a hope of a bright future. Using both illegal and legal ways of migration which has tremendous impact on both sides the home country of the immigrants in terms of loss of human capital also known as brain drain, young population specifically and on the host country where an immigrant could be either a burden to the government or an asset if he or she has outstanding skills that could be needed by the host country.
Keywords: Labor migration; migration theories; migratory processes; economic development